2005
DOI: 10.1007/s10545-006-0292-1
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for medium‐chain acyl‐CoA dehydrogenase deficiency: A global perspective

Abstract: As judged by tandem mass spectrometry blood spot screening, the incidence of medium-chain acyl-CoA dehydrogenase (MCAD) deficiency is 1:14 600 (CI 95%: 1:13 500-1:15 900) in almost 8.2 million newborns worldwide and is 2- to-3 fold higher than that identified in the same populations after clinical presentation. In mass-screened newborn populations, the 985A>G (K329E) mutation accounts for 54-90% of disease alleles, with homozygotes representing about 47-80% of MCAD deficiency cases. Worldwide, octanoylcarnitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 18 publications
4
82
0
3
Order By: Relevance
“…It has been reported that time of sampling affects octanoylcarnitine levels in MCADD (Rhead 2006;Maier et al 2009), but not in unaffected newborns (Khalid et al 2010). As age at sampling did not differ between genotype groups, our collective was eligible for assessment of both the association between biochemical parameters and genotype and biochemical parameters and time of sampling.…”
Section: Time Of Samplingmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that time of sampling affects octanoylcarnitine levels in MCADD (Rhead 2006;Maier et al 2009), but not in unaffected newborns (Khalid et al 2010). As age at sampling did not differ between genotype groups, our collective was eligible for assessment of both the association between biochemical parameters and genotype and biochemical parameters and time of sampling.…”
Section: Time Of Samplingmentioning
confidence: 98%
“…There is ongoing discussion, whether patients with this potentially mild mutation would ever show any clinical phenotype (Andresen et al 2001) or might not require treatment at all (Sturm et al 2012). However, findings on associations between genotype and biochemical phenotype in MCADD are divergent (Andresen et al 1997;Maier et al 2005;Rhead 2006;Sturm et al 2012). A straightforward correlation between clinical phenotype and genotype could not be demonstrated so far (Wilcken et al 1994;Andresen et al 1997).…”
Section: Introductionmentioning
confidence: 96%
“…The clinical phenotypes have recently been associated with a growing number of disorders, such as Reye syndrome, sudden infant death syndrome, cyclic vomiting syndrome, fulminant liver disease, and maternal complications during pregnancy (10). Medium-chain acyl-CoA dehydrogenase (MCAD) deficiency, the most common inherited defect in FAO, causes elevated serum octanoylcarnitine levels (11), reflecting elevated octanoyl-CoA levels. Glutaric aciduria type II (GA2), which is caused by defects in electron transfer flavoprotein (ETF), ETFubiquinone oxidoreductase, or other unknown abnormalities in flavin metabolism or transport, is characterized by elevated serum acylcarnitine levels, including octanoylcarnitine (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is based on cross-sectional data from an unaffected population. However, there have been previous studies examining age variation in C8 concentrations among children with confirmed MCADD (1, 2, 4, 7 ), demonstrating that infants tested at Ͻ10 weeks of age have significantly higher (P Ͻ 0.05) C8 concentrations than those tested at later ages (2 ) and that a 3-fold decline of C8 concentrations is seen over the first weeks of life (11 ). Although C8 concentrations in infants with MCADD are reported to vary by gestational age (7 ), we did not observe such a fall in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, the cutoff used to identify infants in whom MCADD is suspected varies considerably between international screening programs (including those reported from the US, Canada, Germany, Portugal, Italy, Switzerland, and Austria) and ranges from 0.2 to 1.0 mol/L. These values are approximately 4 -11 standard deviations above C8 concentrations seen in unaffected children (11 ). Additionally, results from a screening program in the Netherlands and from a retrospective study of dried blood spots in the UK described a mean value of 6.01 mol/L (3 ) and 3.04 mol/L (2 ), respectively, in affected children with MCADD.…”
Section: Discussionmentioning
confidence: 99%